The Relationship Among Knowledge Ambidexterity, Innovation, and Marketing Performance - Anwar, Yohny; Muis, Indra (Universitas Brawijaya, Indonesia, 2024)
The relationship among knowledge management, organizational ambidexterity, innovation, and marketing performance is crucial in driving organizational success and competitive advantage in today's rapidly changing business environment. The aim of the study is to look at relationship knowledge management, organizational ambidexterity, innovation, and marketing performance. Besides, it examines the effects of knowledge management and organizational ambidexterity on marketing performance as intervened by innovation as a mediator. The unit analysis is the owners of SMEs in Medan Municipality, North Sumatra Province, Indonesia. This research applies quantitative methods. The research population was 478 SMEs in technology and internet businesses registered in the Government Office of Cooperatives and Micro, Small, and Medium Enterprises (MSME) of Medan, North Sumatra, Indonesia. The respondents were 217 owners of SMEs. The sampling technique is simple random sampling. The data analysis uses the Partial Least Square technique. The research finds that both knowledge management and organizational ambidexterity have positive impacts on innovation. Innovation mediates the knowledge management-marketing performance relationship and organizational ambidexterity-marketing performance relationship. It is advisable for Small Medium Business owners to implement knowledge management, organizational ambidexterity, and innovation to increase their marketing performance.